2005
DOI: 10.1074/jbc.m411898200
|View full text |Cite
|
Sign up to set email alerts
|

Iso-coenzyme A

Abstract: Iso-coenzyme A is an isomer of coenzyme A in which the monophosphate is attached to the 2-carbon of the ribose ring. Although iso-CoA was first reported in 1959 (Moffatt, J. G., and Khorana, H. G. (1959) J. Am. Chem. Soc. 81, 1265-1265) to be a by-product of the chemical synthesis of CoA, relatively little attention has been focused on iso-CoA or on acyl-iso-CoA compounds in the literature. We now report structural characterizations of iso-CoA, acetyl-iso-CoA, acetoacetyl-iso-CoA, and ␤-hydroxybutyryl-iso-CoA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…The 2′-phosphate isomer of coenzyme A isomer is called isocoenzyme A [25]. Burns and coauthors [16] separated CoASH and iso-CoASH as well as several pairs of acylCoA and acyl-iso-CoA in commercially available standards via RPLC and characterized those using MS/MS and NMR. They discovered that iso-CoAs acted as substrates instead of CoAs in enzyme-catalyzed reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2′-phosphate isomer of coenzyme A isomer is called isocoenzyme A [25]. Burns and coauthors [16] separated CoASH and iso-CoASH as well as several pairs of acylCoA and acyl-iso-CoA in commercially available standards via RPLC and characterized those using MS/MS and NMR. They discovered that iso-CoAs acted as substrates instead of CoAs in enzyme-catalyzed reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Reversed phase liquid chromatography employing ion-pairing reagents (ion-pair RPLC) was addressed as the method of choice suitable for a broad spectrum of short-chain acyl-CoA analysis [11,12,13,14,15]. Alternately, a comparatively smaller selection of these target metabolites has been separated by reversed phase liquid chromatography without the use of ion-pairing reagents [16,17,18,19]. In studies where short-chain acyl-CoAs were measured within a comprehensive primary metabolome analysis, ion-pair RPLC was applied [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…These data indicated that BrPA was directly interfering with CoA at its free thiol group. Using a previously published ionization pattern for CoA (29), we demonstrated by mass spectrometry that pyruvylation occurs at the sulfhydryl group of CoA (Supplementary Fig. S6).…”
Section: Brpa Inhibits Dnl By Pyruvylation Of Coamentioning
confidence: 99%
“…These species were absent in control samples and their MS/MS fragmentation pattern was consistent with that of coenzyme A derivatives. [43] While the assignment of m/z 922 (Figure 1 A) and 964 (Figure 1 B) to the diketide 21 a and the triketide 22 a, respectively, was clear-cut, two distinct peaks were found for m/z 1006 at 15.9 and 19.9 min (Figure 1 C and E). Their different MS/MS fragmentation patterns allowed their assignment to the nonhydrolyzable tetraketide 23 a (Figure 1 C) and to the dehydrated, possibly cyclized, natural tetraketide 25, respectively (Figure 1 E), with the latter showing the m/z 768 fragment diagnostic for a coenzyme A thioester.…”
Section: Trapping Polyketide Intermediates Of the Sts Reactionmentioning
confidence: 92%